2023
DOI: 10.7150/ijbs.76798
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of IGF2BP1 by USP10 promotes breast cancer metastasis via CPT1A in an m6A-dependent manner

Abstract: Metastasis leads to the vast majority of breast cancer mortality. Increasing evidence has shown that N6-methyladenosine (m6A) modification and its associated regulators play a pivotal role in breast cancer metastasis. Here, we showed that overexpression of the m6A reader IGF2BP1 was clinically correlated with metastasis in breast cancer patients. Moreover, IGF2BP1 promoted distant metastasis in vitro and in vivo. Mechanistically, we first identified USP10 as the IGF2BP1 deubiquitinase. USP10 can bind to, deubi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 79 publications
0
9
0
Order By: Relevance
“…Studies have shown that there is a crosstalk between RNA m 6 A modification and protein ubiquitination (Shi et al 2023 ; Zhang et al 2022b ), but the relationship between RNA m 6 A modification and protein ubiquitination is not clear. In our study, we found that m 6 A was located upstream of ubiquitination.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that there is a crosstalk between RNA m 6 A modification and protein ubiquitination (Shi et al 2023 ; Zhang et al 2022b ), but the relationship between RNA m 6 A modification and protein ubiquitination is not clear. In our study, we found that m 6 A was located upstream of ubiquitination.…”
Section: Discussionmentioning
confidence: 99%
“…Carnitine palmitoyltransferase (CPT) facilitates the transport of long-chain fatty acids across the mitochondrial membrane, where they undergo β-oxidation to generate acetyl-CoA and produce ATP (Figure 1C). In breast cancer, the stabilisation of CPT1A mRNA by IGF2BP1 leads to an increase in cell migration and invasion [90]. The inhibition of CPT1A expression decreases proliferation and tumorigenicity in melanoma cells [91].…”
Section: Altered Fatty Acid Oxidationmentioning
confidence: 99%
“…Functionally, IGF2BPs mainly recognizes and binds mRNA through KH domain, thus enhancing the stability of m6A-modified mRNA and improving the translation efficiency of mRNA, thus regulating various physiological and pathological functions. IGF2BP1 has been identified to play an important role in the regulation of mRNA targets such as CPT1A, E2F1, PEG10, c-MYC, and CCL5 in an m6Adependent manner [13][14][15][16]. Zhou et al reported that METTL3 promotes osteoblast differentiation of bone marrow mesenchymal stem cells (BMSCs) through IGF2BP1-mediated Runx2 mRNA stabilization to regulate osteogenic responses [17].…”
Section: Ivyspringmentioning
confidence: 99%